Design, analysis and fabrication of mini curry puff machine / Aliah Maisarah Nordin and Ahmad Najmie Rusli - Nordin, Aliah Maisarah; Rusli, Ahmad Najmie (School of Mechanical Engineering, 2022)
Curry puffs were popular, particularly in Asian countries. Traditional methods, which took a lot of time and effort, were used by the older generation to prepare certain delights. However, mankind has progressed to the point where they have been able to develop and invent a tool to flatten the dough for curry puffs. As a result, the time and energy required to manufacture curry puffs were reduced. Albeit of the tools being created, there are still limitations and hindrances which affect mankind’s health. Therefore, the purpose of this project is to encounter all of the obstacles effortlessly. The product from this project is able to assist people in making curry puffs with a little bit of effort as well as the product is very portable and lightweight.